Creating Markets in Pakistan : Bolstering the Private Sector - International Finance Corporation (International Finance Corporation, Washington, DC, 2022)
This Country Private Sector Diagnostic (CPSD) analyzes and synthesizes cross-cutting and sectoral impediments to private sector development in Pakistan. It also proposes a policy reform agenda that would be transformational for the growth and competitiveness of the private sector. It complements the World Bank’s Systematic Country Diagnostic (SCD, 2020) and aims to contribute to the national dialogue by focusing specifically on private sector issues. The Pakistan@100 body of work is the base and it draws on recent thematic World Bank reports and consultations with business leaders and public officials. Technical solutions to Pakistan’s institutional constraints and policy distortions are readily available, but the implementation of these solutions requires committed political leadership. This has proven hard to muster in Pakistan’s young and noisy democracy. Successive administrations have been humbled by vocal public opposition or internal resistance to change influenced by special interest groups. Maintaining political stability has been challenging with frequent transfers of power between civilian and military administrations. The devolution of powers to the provinces and local governments has resulted in an institutional footprint with sometimes overlapping or unclear mandates that give rise to uncertainty for businesses. The question is therefore what it would take for Pakistan’s policymakers—and its elites and informal decision makers—to step up to address the multitude of issues as Pakistan falls behind its peers. Or, in other words, what would enable the government to break the economy’s many sub-optimal equilibria.